Stimulant pharmacotherapy for adults with attention deficit hyperactivity disorder: cardiovascular effects and risk of sudden cardiac death. (August 2016) - Pucci, Mark
Abstract : Summary: Drugs for attention deficit hyperactivity disorder are increasingly being used in adults. There have been concerns about the cardiovascular safety of stimulant attention deficit hyperactivity disorder drugs. Overall, studies in adults have shown small but statistically significant increases in heart rate and DBP and SBP, but have been relatively short term. Epidemiological studies have not clearly demonstrated an increased risk of sudden cardiac death, but a small increase in the risk cannot be ruled out.